2016
DOI: 10.1038/srep32085
|View full text |Cite
|
Sign up to set email alerts
|

Induction of renal senescence marker protein-30 (SMP30) expression by testosterone and its contribution to urinary calcium absorption in male rats

Abstract: The aim of this study was to investigate the involvement of androgen, mainly testosterone, in the expression of renal senescence marker protein-30 (SMP30) in male rats. We found that the renal SMP30 expression was up-regulated by endogenous testosterone stimulation during puberty. Interestingly, androgen-deficient orchidectomized (ORX) rats exhibited lower SMP30 mRNA and protein expression in the kidney, and that was restored by testosterone propionate (TP) replacement. Abrogation of androgen receptor (AR) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…This metal-dependent enzyme promiscuity is responsible for a regulatory mechanism which allows a single enzyme to specifically control different metabolic pathways and produce different metabolites [21,26,27]. This study also supports the importance of HuSMP30 in the calcium homeostasis as it has shown significantly high binding affinity (Kd = 0.29 ± 0.13 μM, Table 1 ) with Ca 2+ [2830].…”
Section: Discussionsupporting
confidence: 69%
“…This metal-dependent enzyme promiscuity is responsible for a regulatory mechanism which allows a single enzyme to specifically control different metabolic pathways and produce different metabolites [21,26,27]. This study also supports the importance of HuSMP30 in the calcium homeostasis as it has shown significantly high binding affinity (Kd = 0.29 ± 0.13 μM, Table 1 ) with Ca 2+ [2830].…”
Section: Discussionsupporting
confidence: 69%
“…We speculated that this could have been due to the following reasons: (1) The affinity of testosterone for the AR in NRK52E cells may be comparatively lower than that in RMC cells; and (2) The main function of the AR in NRK52E cells may be biased toward being associated with other physiological roles. The literature demonstrates that NRK52E cells are directly associated with testosterone-induced senescence 28 , while expression of the renal senescence marker protein, SMP30, was upregulated by endogenous testosterone stimulation; the latter increases renal anti-aging klotho gene expression via an AR-mediated pathway 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Radioimmunoassay (RIA) of testosterone. The concentrations of testosterone in the culture medium and plasma were determined by RIA as previously described 60 . Using an anti-testosterone serum (No.…”
Section: Preparation Of Rat Primary Leydig Cellsmentioning
confidence: 99%
“…Western blot, as described previously 60 . Briefly, quantitative amounts of samples (60 μg) were mixed with a sample buffer (0.125 M Tris-Cl pH 6.8, 20% glycerol, 4% sodium dodecyl sulfate (SDS), 10% 2-mercaptoethanol, 0.1% bromophenol blue) at a ratio of 1:1.…”
Section: Protein Preparation and Western Blot Analysis Total Cell Anmentioning
confidence: 99%